Productivity and Suitability Evaluation of Orange (Citrus reticulata)-Growing Soils of Hot and Semi-Arid Region of Rajasthan (AESR 5.2) - and R.S. Garhwal, Rameshwar Singh, R.S. Singh, H.S. Purohit, T.P. Verma (Journal of the Indian Society of Soil Science, 2016)
Fourteen pedons were evaluated for their productivity and suitability on the basis of variation in physiography, parent materials, soils and productivity of orange in Jhalawar district of Rajasthan. The pedons were developed by sandstone and shale (P1–P6) and basalt parent materials (P7-14) in Vindhyan and Malwa region, respectively and classified as Vertisols (P3, P5, P7-P13) and Inceptisols (P1, P2, P4, P6 and P14). In general, sand silt and clay contents ranged from 3.4 to 48.1, 27.8 to 71.0 and 18.6 to 60.9% in different horizons, respectively. The soils were calcareous and moderately alkaline to strongly alkaline in reaction and sub-soil sodicity is just arising mostly in soils of Malwa region (P3, P9 and P12). The organic carbon ranged from 0.36 to 9.13 g kg-1 and cation exchange capacity from 22.5 to 62.5 cmol(p+)kg-1 soil. The soils were low to optimum in available N and K and low to excess in available P. The Riquier productivity index appears to be more reliable as compared to Storie index and these ratings are not in reliance with the Sys and proposed suitability criteria and yield of orange realized. On computation of the existing limitations, a new criterion has been proposed (against Sys suitability criteria for citrus species) which indicated that P2, P3, P7, P9, P10, P11 and P12 were moderately suitable, P1, P4-P6, P8, P13 and P14 were suitable for orange production.